Investigation of film cooling effectiveness from cylindrical cooling hole with anti vortex generator by numerical simulation - Abu Zarida, Abdallah Ali (2015)
This study deals numerical study of the effect of anti vortex generator (AVG) on the film cooling performance of a circular cooling hole which has diameter (d = 20 mm) on a flat plate. The interaction between the jet cooling air and mainstream will result kidney vortex which will eliminate the film cooling effectiveness. Two types of AVG with different heights (H = 0.5 d and 0.25 d) are designed to eliminate the kidney vortex and investigate best film cooling effectiveness, where each of them is mounted to the flat plate upstream of the cooling hole by changing its lateral positions (A = 0.0 d, 0.25 d, 0.5 d and 0.75 d) with respect to the hole centerline and for each type has different distance respect to hole centerline. The changing of blowing ratio (BR = 0.5-1.5) was considered in this study. As for the validation, the present study was compared with the previous research done by other researchers using the results obtained from experimental data. The steady turbulence model shear stress transport (SST) that was used to simulate a film cooling configuration. The results have been presented in terms of laterally averaged film cooling comparison graphs, velocity field on x/d = 3.0, non-dimensional temperature on x/d = 3.0 and the vorticity on x/d = 3.0 which explained how the results obtained. Cases 04 and 07 gave the best positions for AVG where case 04 gave wide covered for laterally average film cooling effectiveness , while case 07 gave the highest expand distribution and the maximum value for film cooling effectiveness .